Harmonic Rhythm: The Essence of an Enjoyable Design Process - Amos Ih-Tiao Chang (Oz, 1985)
While production efficiency is the rule of modern life, design efficiency has not reached the happy level it could when dealing with the human actors of our environment because the process of design - and the production of a design - is not exactly an enjoyable one...